Highly sensitive fiber grating hydrogen sensor based on hydrogen-doped Pt/WO3 - Wang, Chaoqin; Han, Zewen; Wang, Chenxiang; Peng, Gang-Ding; Rao, Yun-Jiang; Gong, Yuan (Sensors and actuators. B, Chemical, 2024)
Hydrogen sensors are key to the emerging clean hydrogen economies and fiber-optic hydrogen sensors play a unique role owing to their inherent safety and high sensitivity. Currently Pt/WO3 has been employed as the mainstream hydrogen-sensitive material in high performance hydrogen sensors. Here we develop an ultrasensitive fiber-optic hydrogen sensor with fast response by coating pretreated Pt/WO3 nanomaterial on fiber Bragg grating. We observe a great enhancement in sensitivity by the hydrogen-doping of the Pt/WO3 nanomaterials. The generation of HxWO3 composite material is confirmed by XRD, FTIR and Raman analysis. Compared with pure Pt/WO3, a 184-fold improvement in sensitivity is achieved by hydrogen doping, with a fast response of 25 s. An impressive limit of detection (LOD) of 30 ppm is demonstrated by employing both the narrowband weak FBGs and the hydrogen-doped Pt/WO3. The immunity to ambient temperature fluctuation is demonstrated by self-calibration through detecting the wavelength difference between a pair of FBGs. Good specificity is also demonstrated. This technology shows great potential in high spatial-resolution quasi-distributed hydrogen sensing. •A new pre-treatment method for hydrogen-sensitive materials has been proposed, and the sensitivity increased by 184 times.•The trade-off between response time and limit of detection (LOD) has been resolved.•The quasi-distributed hydrogen sensing has been achieved through the wavelength division multiplexing technology.•The temperature compensation has been achieved and repeatable hydrogen tests were demonstrated under different temperatures.